2017
DOI: 10.17116/jnevro20171175152-57
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and antidepressant effects of emoxipine, reamberin and mexidol in experimental diabetes mellitus

Abstract: All studied medications used in doses equivalent to therapeutic range in humans and administered for 14 days significantly reduced manifestations of anxiety and depression in rats with alloxan diabetes. The most pronounced anxiolytic potential was demonstrated for emoxipine that emerged as the only medication in the study that reduced manifestations of anxiety not only in comparison with 'alloxan diabetes-control' groups but also in comparison to 'intact control'. The intensity of tranquilizing activity of der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…An alternative approach to pharmacotherapy of DN complications could conclude in using 3-oxypyridine derivatives, particularly methylethylpiridinol hydrochloride. Experimental studies showed its potentiating activity towards insulin, capacity for increasing tolerance to glucose loading, antihypoxic and neuroprotective action in acute cerebrovascular pathologies [11].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to pharmacotherapy of DN complications could conclude in using 3-oxypyridine derivatives, particularly methylethylpiridinol hydrochloride. Experimental studies showed its potentiating activity towards insulin, capacity for increasing tolerance to glucose loading, antihypoxic and neuroprotective action in acute cerebrovascular pathologies [11].…”
Section: Introductionmentioning
confidence: 99%